Related Fisheries Management of Fish and Phytoplankton Biodiversity with Relationship to Primary Productivity of the Govardhan Sagar Lake, Udaipur, Rajasthan - A., Bhatt Nakul; Kumawat, T.; Singh, E.; Priyadarshini, A. (International Journal of Bio-resource and Stress Management, 2019)
The present study on the related fisheries management of fish and phytoplankton biodiversity with relationship to primary productivity of the Goverdhan sagar Lake was conducted during October 2017 to September 2018. The Lake has a fairly rich fish fauna and so far, 18 species representing 6 families have been recorded in the present investigation, of these, 9 species predominantly contributed to the commercial fisheries of the Lake. In the present study, water quality parameters such as transparency, pH, alkalinity, free carbon dioxide, air and water temperature, dissolved oxygen, primary productivity, conductivity, nitrate-nitrogen, and orthophosphate were done along with qualitative and quantitative estimation of phytoplankton. The study indicated that the average primary productivity (GPP) of the Goverdhan sagar Lake was found to be 0.70 g cm3 h-1, NPP (0.57 g cm3 h-1) and CR was found to be 0.27 g cm3 h-1 in the surface. Algae in fresh water have numerous environmental functions and are based upon the recycling of nutrients. Totally 36 species of phytoplankton belonging to different taxonomic group were identified. Among these 09 species to belong to Bacillariophyceae, 12 species to chlorophyceae, 12 species to cyanophyceae and 03 speceis to desmidiaceae. The Indian major carps were dominated the catch by contributing 85% of the total landings from the Lake whereas minor carps and catfishes were reported as 8.5% and 6.5% respectively.